2012
DOI: 10.3109/15563650.2011.649092
|View full text |Cite
|
Sign up to set email alerts
|

Acute intoxications: Differences in management between six Dutch hospitals

Abstract: Context . Acute intoxications are frequently seen in Dutch hospitals. Based on single-centre studies and the fact that there are no clear guidelines, we hypothesised that hospital admission of acute intoxications may vary. Furthermore, decontamination treatment of poisonings may differ between hospitals, as earlier studies showed that adherence to international guidelines concerning decontamination may be poor. Objective . We aim to identify possible variations in Dutch hospital admission and decontamination t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…The mean age average of 37 years in our study was within the range of most studies (33-40y) [3,4,10,11,14,17,18,32] although some studies found a lower mean age (range 23-28y) [2,5,12].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The mean age average of 37 years in our study was within the range of most studies (33-40y) [3,4,10,11,14,17,18,32] although some studies found a lower mean age (range 23-28y) [2,5,12].…”
Section: Discussionsupporting
confidence: 73%
“…In the Netherlands, Duineveld et al [4] analysed acute intoxications in six hospitals. They reported the use of ethanol whether or not in combination with other drugs in 318/1,183 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these severity scores are not relevant in ED daily practice because they underestimate DDP mortality, they usually predict outcome 24 hr after admission and they rely on complex algorithms and biological data [17][18][19]. This lack of validated severity score leads to significant variations in the management of poisoned patients and to potential inappropriate use of medical resources [20]. The purpose of this study was therefore to identify simple factors associated with intensive care unit (ICU) admission that could help physicians in the triage of DDP patients without obvious life-threatening symptoms on ED admission.…”
mentioning
confidence: 99%
“…In addition, there is a higher use of antipsychotics in men compared to women, and men are known also to adhere to medication more consistently [25]. Also, in a study on acute intoxications in six Dutch hospitals, intoxications due to substance abuse was more frequently seen in men (66.0%) [26].…”
Section: Discussionmentioning
confidence: 99%